Socio-demographic selectivity of Returnees - Mesić, Milan, sociolog (2009)
The presentation is based on the representative filed research commissioned by the UNHCR, office in Zagreb, conducted by the authors in the autumn 2007 among the Serb returnees to Croatia. Two major questions underlie the survey: how many returnees really live in Croatia, and who they are in terms of their socio-demographic characteristics The presentation deals with the socio-demographic selectivity of the returnees. Generally, the findings clearly indicate that significantly greater inclination to stay permanently demonstrate rural, uneducated older people. In short, it has been shown that (permanent) returnees (just like return migrants in general) are highly negatively selected with respect to age, education, qualification, family situation and some other vital features.